2007
DOI: 10.1038/sj.bjc.6603943
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled study of an audiovisual patient information intervention on informed consent and recruitment to cancer clinical trials

Abstract: Recruitment to cancer clinical trials needs to be improved, as does patient knowledge and understanding about clinical trials, in order for patients to make an informed choice about whether or not to take part. Audiovisual patient information (AVPI) has been shown to improve knowledge and understanding in various areas of practice, but there is limited information about its effect in the cancer clinical trial setting, particularly in relation to consent rates. In this study, 173 patients were randomised to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
86
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 29 publications
7
86
0
2
Order By: Relevance
“…Although tests and scoring systems differ, studies of general patient populations have shown similar results 11,17,18 . By comparison, a study involving participants in clinical trials showed higher knowledge scores 22 , consistent with a similar subset in our data.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Although tests and scoring systems differ, studies of general patient populations have shown similar results 11,17,18 . By comparison, a study involving participants in clinical trials showed higher knowledge scores 22 , consistent with a similar subset in our data.…”
Section: Discussionmentioning
confidence: 65%
“…Education can improve apparent willingness to join a clinical trial 2,18,20,21 , but it is not clear that such willingness translates into improved trial recruitment 2,17,20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results correlate with research performed in other countries. Some previous studies revealed that providing the patient with audiovisual information is effective in giving the patient knowledge and understanding before signing the statement of informed consent [4,5] in many different kinds of surgeries such as; laparoscopic cholecystectomies [6,7], gastric banding, knee arthroscopies, and central venous catheterizations. These studies found that the use of multimedia help the patient to gain a better understanding of the disease process and the surgical proce-dure, without experiencing any more anxiety that those not receiving the information materials [8][9][10].…”
Section: Discussionmentioning
confidence: 99%